"Erratum: What Was an Early Modern Public, and How Was It Made?". Issue 1 (11th January 2013) - McKeon, Michael
Abstract: One argument of The Secret History of Domesticity is that there were two early modern publics, one traditional and one innovative; that the new concept of the public began to emerge when the authority of the old public, until then a matter of tacit belief, was subjected to explicit and rational analysis; and that the rationality of the new public depended on the simultaneous rise of an entirely new concept, the private. This argument responds at length to the central question raised by the Making Publics Project –''What was an early modern public, and how was it made?''– in ways that are pertinent to the work of MaPs, as can be seen in the stimulating essays gathered for this collection. The contributors have focused on a broad range of issues entailed in the hypothesis of a modern public, from political and religious history, social theory, historiography, and periodization to the history of civic architecture, gender and domesticity, drama, and the aesthetic, principally in England but also in fourteenth‐century Italy and the seventeenth‐century Dutch Republic. This comparative dimension enhances and deepens the developing coherence, within English culture, of the category of the modern.